Understanding why people value working from home or hybrid workplace flexibility a study of preferences during the COVID-19 pandemic - Courtney Bir; Jinho Jung; Nicole Olynk Widmar (PLoS ONE, 2026)
Working-From-Home (WFH) practices expanded rapidly during the COVID-19 pandemic and continue to be a point of discussion today with debates increasingly focused on productivity rather than the underlying reasons for WFH or flexibility. This study investigates why individuals value WFH and hybrid work arrangements in the United States. The specific period of study was during the COVID-19 pandemic. Understanding these motivations can inform constructive negotiations and effective policies that enhance productivity while supporting employees’ work–life balance and caregiving responsibilities. Despite extensive discussion of whether employers should permit WFH, the diverse reasons employees seek flexibility remain understudied. Using data from a nationally representative online survey conducted in late 2021, we employ a best–worst scaling experiment to rank motivations for remote work. Results show the most valued reason for WFH is balancing work with caregiving, followed by reducing commuting time and costs, limiting exposure to illness, and preferring the home environment. A latent class model identifies four heterogeneous preference segments: (1) caregiving and commuting, (2) productivity and comfort, (3) multitasking and health safety, and (4) diffuse preferences without a dominant motivation. Additionally, seemingly unrelated regression analysis links WFH preferences with behavioral changes in grooming, attire, and personal care routines. These findings highlight the heterogeneity in workers’ motivations for flexibility and suggest that one-size-fits-all approaches may be inefficient. By revealing the underlying drivers of WFH preferences, this study offers nuanced insights for organizations seeking to design flexible work policies that balance productivity objectives with employee well-being.